Black rice : the African origins of rice cultivation in the Americas - Carney, Judith Ann (ACLS Fellows' publications., 2001)
"Through agricultural and historical evidence, [the author establishes] the independent domestication of rice in West Africa and its vital significance there for a millennium before Europeans arrived and the slave trade began."--Jacket.